CONNECTION APPROACHES BETWEEN TRADITIONAL AND MODERN PHARMACOLOGICAL PROFILE OF SHOREA ROBUSTA GAERTN. F.: A REVIEW - Singh, Manish Pal; Kumar, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Shorea robusta is regarded as an important medicine in Ayurveda. S. robusta Gaertn. f. belongs to family Dipterocarpaceae, and traditionally, it is used to treat wounds, ulcers, leprosy, cough, gonorrhea, earache, and headache and many more. The use of different parts of this plant such as leaves, resin, and bark as a medicament for the treatment of various conditions is well documented in literature. It is the rich source of flavonoids, saponins, steroids, tannins, phenols, etc. mainly triterpenoids, which play the prominent role for their therapeutic potential in the drug. These compounds are believed to be responsible for the pharmacological activities of plant extract. The present review clarified the main active ingredients and pharmacological effects of S. robusta as a promising plant as a result of effectiveness and safety. Further studies should be carried out this plant to discover the unrevealed part of it which may serve for the welfare of humankind.